Automatic Wadding of Rice in Small Scale Industries - Aravind C., Suji Prasad S. J., Aarthi J., Lavanya M., Madhan Kumar T (International Journal of Control and Automation, 2020)
Automation plays a major role in most of the industrial applications. The small and medium scale industries contribute more to the country’s economy. The small scale industries like rice mills suffer a lot without automation of plants. Opening of empty bags, filling of rice from hopper and packing are the main process involved in the packing of rice. The opening of an empty bag is one of the processes which consumes manpower and the workmen are affected by dust pollution. This work proposes an automatic system for opening and filling of rice which reduces the manpower. This paper details the system that works with pneumatic cylinders, suction cup, dc motor, piston and microcontroller.